2002
DOI: 10.1142/s0217979202015315
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Assembly of Porous Silicon

Abstract: Electrophoretic assembly of porous silicon (PS) has been studied in the present paper. A toluene/porous silicon suspension was prepared by the sonication of anodically etched porous silicon wafers and showed a PL property similar to the as-prepared PS, giving 620nm orange-red photoluminescence emissions. A broad optical absorption band about 286nm arising from scattering and absorption of the light by the PS particles has been observed. The PS particles suspended in toluene drifted towards the positive electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…12) The band at 1109 cm À1 corresponds to the vibration absorption of Si-O bonds. 13) It can be observed that a weak and broad band at 558 cm À1 corresponds to the stretching vibration absorption of Ga-N bonds in a hexagonal GaN crystal, 14) indicating that there are a small number of Ga-N bonds in the films. Figure 3(b) shows the FTIR spectrum of the GaN films annealed at 950 C for 15 min in high-purity ammonia ambience.…”
Section: Ftir Analysismentioning
confidence: 99%
“…12) The band at 1109 cm À1 corresponds to the vibration absorption of Si-O bonds. 13) It can be observed that a weak and broad band at 558 cm À1 corresponds to the stretching vibration absorption of Ga-N bonds in a hexagonal GaN crystal, 14) indicating that there are a small number of Ga-N bonds in the films. Figure 3(b) shows the FTIR spectrum of the GaN films annealed at 950 C for 15 min in high-purity ammonia ambience.…”
Section: Ftir Analysismentioning
confidence: 99%
“…We have previously studied the photoluminescence, electrophoretic assembly and photoluminescent enhancement properties of porous silicon based on n-type single-crystal (111) silicon wafers [23][24][25]. In this study, In this work, we have fabricated a unique electrode based on aminopropyl-triethoxysilane(APTS)-coated porous silicon(PS) substrate and used it as a urea-sensitive electrode after urease immobilization.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously studied the photoluminescence properties of porous silicon based on n-type single-crystal (111) silicon wafers [27][28][29] and used the electrolysis technique to prepare zinc oxide nanoparticles suspended in ethanol solution and of zinc oxide powder with strong photoluminescence (PL) at room temperature [30]. In this paper, we will present the formation of transparent ZnO films from zinc nitrate aqueous solution by pulsed current of rectangular wave and the modification of porous silicon with the ZnO films based on the cathodic electrochemical deposition technique.…”
Section: Introductionmentioning
confidence: 99%